1976
DOI: 10.1070/rc1976v045n01abeh002595
|View full text |Cite
|
Sign up to set email alerts
|

Xylitol and Its Derivatives

Abstract: The literature data on the pentahydric alcohol xylitol are reviewed. The methods for the preparation of xylitol, its ethers, esters, nitrogen-, halogen-, and sulphur-containing derivatives, acetals, ketals, anhydroxylitols, and their various derivatives are examined and the spectroscopic methods for demonstrating the structures of certain xylitol derivatives are discussed. The therapeutic and diagnostic, dietary, and industrial applications of xylitol and its derivatives are briefly considered. The bibliograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 199 publications
0
3
0
Order By: Relevance
“…These were almost completely eliminated after alkaline extraction, as seen in Pulp-2 (Figure b, d, and f). It had been reported that after alkaline extraction lignin may be reabsorbed from the alkaline extraction liquor to cellulose fibers, but this cannot be seen in the SEM images because of their resolution limit …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These were almost completely eliminated after alkaline extraction, as seen in Pulp-2 (Figure b, d, and f). It had been reported that after alkaline extraction lignin may be reabsorbed from the alkaline extraction liquor to cellulose fibers, but this cannot be seen in the SEM images because of their resolution limit …”
Section: Resultsmentioning
confidence: 99%
“…It had been reported that after alkaline extraction lignin may be reabsorbed from the alkaline extraction liquor to cellulose fibers, but this cannot be seen in the SEM images because of their resolution limit. 3 Post-Treatment of Liquor Obtained from Hydrothermolysis Pretreatment. Liquor-1 was mainly composed of xylose and xylo-oligomers, which together were equivalent to 22.8 g/L of xylose.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
See 1 more Smart Citation